High performance synthetic fiber-reinforced concrete mixed with nanoparticles: A proof-of-concept green railway sleeper product - Radhika Sridhar; Satjapan Leelatanon; Monthian Setkit; Thanongsak Imjai; Elhem Ghorbel; Boksun Kim (Sustainable Structures)
This paper investigates the effects of nanoparticles and fibers on the durability and microstructural properties of mortar and concrete, aiming to create a high-performance railway sleeper product as an alternative sustainable material in the market. In the Phase 1, the main objective is to evaluate the effectiveness of nanoparticles, such as nano alumina (NA) and nano silica (NS), at 1%, 3%, and 5% additions, along with rice husk ash (RHA) and ground granulated blast furnace slag (GGBFS) in terms of strength and durability performance. To further enhance structural integrity, the study incorporates fibers such as polypropylene fiber (PPF) and polyvinyl alcohol fiber (PVA) at a constant volume fraction of 0.5%. The hybridization of NA and NS with PPF and PVA fibers was developed and analyzed through scanning electron microscopy (SEM) and energy dispersion X-ray (EDX) analysis. The mechanical property tests revealed that hybrid nanoparticles enhanced compressive strength by 15% compared to control and mono nanoparticle composites. Durability tests, including water absorption, rapid chloride penetration, and water penetration, showed that adding 5% hybrid nanoparticles and 0.5% fibers resulted in high strength (17.81%) and significant pre refinement. In Phase 2, a proof-of-concept green railway sleeper was developed using 100% recycled aggregate concrete (RAC), reinforced with glass fiber-reinforced polymer (GFRP) and the hybrid fibers from Phase 1, demonstrating enhanced mechanical properties and durability. Additionally, finite element crack analysis using Abaqus® software provided an in-depth understanding of sleeper performance, revealing improved crack resistance under operational fatigue loading and reduced maintenance costs. This innovative approach showcases a sustainable product with superior performance, addressing both environmental and structural challenges in railway infrastructure.